Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 45232 by maxmathsup by imad last updated on 10/Oct/18

calculate  ∫_0 ^1 ln(x)ln(1+x)dx .

calculate01ln(x)ln(1+x)dx.

Commented by maxmathsup by imad last updated on 11/Oct/18

let I = ∫_0 ^1 ln(x)ln(1+x)dx  we have for ∣x∣<1  ln^′ (1+x)=Σ_(n=0) ^∞  (−1)^n x^n  ⇒ln(1+x)=Σ_(n=0) ^∞  (((−1)^n )/(n+1))x^(n+1)  +λ  x=0 ⇒λ=0 ⇒ln(1+x) =Σ_(n=1) ^∞  (((−1)^(n−1) )/n) x^n  ⇒  I =Σ_(n=1) ^∞  (((−1)^(n−1) )/n) ∫_0 ^1  x^n ln(x)dx  by parts  A_n =∫_0 ^1 x^n ln(x)dx =[(1/(n+1))x^(n+1) ln(x)]_(x→0) ^1  −∫_0 ^1 (1/((n+1))) x^n dx  =−(1/((n+1)^2 )) ⇒I =Σ_(n=1) ^∞  (((−1)^n )/(n(n+1)^2 ))  let decompose F(x)=(1/(x(x+1)^2 ))  F(x)=(a/x) +(b/(x+1)) +(c/((x+1)^2 ))  a =lim_(x→0) xF(x)=1  c =lim_(x→−1) (x+1)^2 F(x)=−1 ⇒F(x)=(1/x) +(b/(x+1)) −(1/((x+1)^2 ))  F(1) =(1/4) =1 +(b/2) −(1/4) ⇒1 =4+2b−1 =3+2b ⇒2b=−2 ⇒b=−1 ⇒  F(x) =(1/x) −(1/(x+1)) −(1/((x+1)^2 )) ⇒  I =Σ_(n=1) ^∞  (((−1)^n )/n) −Σ_(n=1) ^∞  (((−1)^n )/(n+1)) −Σ_(n=1) ^∞  (((−1)^n )/((n+1)^2 )) but  Σ_(n=1) ^∞   (((−1)^n )/n) =−ln(2)  Σ_(n=1) ^∞   (((−1)^n )/(n+1)) =Σ_(n=2) ^∞    (((−1)^(n−1) )/n)  = ln(2)−1  Σ_(n=1) ^∞   (1/((n+1)^2 )) =Σ_(n=2) ^∞   (((−1)^n )/n^2 ) = Σ_(n=1) ^∞  (((−1)^n )/n^2 ) +1  let find Σ_(n=1) ^∞  (((−1)^n )/n^2 )  we have Σ_(n=1) ^∞    (((−1)^n )/n^2 ) =Σ_(n=1) ^∞  (1/((2n)^2 )) −Σ_(n=0) ^∞  (1/((2n+1)^2 ))  =(1/4) (π^2 /6) −Σ_(n=0) ^∞   (1/((2n+1)^2 )) but Σ_(n=1) ^∞  (1/n^2 ) =(1/4) Σ_(n=1) ^∞  (1/n^2 ) +Σ_(n=0) ^∞  (1/((2n+1)^2 )) ⇒  Σ_(n=0) ^∞  (1/((2n+1)^2 )) =(3/4) Σ (1/n^2 ) =(3/4) (π^2 /6) =(π^2 /8) ⇒Σ_(n=1) ^∞ (((−1)^n )/n^2 ) =(π^2 /(24)) −(π^2 /8) =−(π^2 /(12)) ⇒  ∫_0 ^1 ln(x)ln(1+x)dx =−ln(2)−ln(2)+1 −(−(π^2 /(12))+1)  =(π^2 /(12)) −2ln(2) .

letI=01ln(x)ln(1+x)dxwehaveforx∣<1ln(1+x)=n=0(1)nxnln(1+x)=n=0(1)nn+1xn+1+λx=0λ=0ln(1+x)=n=1(1)n1nxnI=n=1(1)n1n01xnln(x)dxbypartsAn=01xnln(x)dx=[1n+1xn+1ln(x)]x01011(n+1)xndx=1(n+1)2I=n=1(1)nn(n+1)2letdecomposeF(x)=1x(x+1)2F(x)=ax+bx+1+c(x+1)2a=limx0xF(x)=1c=limx1(x+1)2F(x)=1F(x)=1x+bx+11(x+1)2F(1)=14=1+b2141=4+2b1=3+2b2b=2b=1F(x)=1x1x+11(x+1)2I=n=1(1)nnn=1(1)nn+1n=1(1)n(n+1)2butn=1(1)nn=ln(2)n=1(1)nn+1=n=2(1)n1n=ln(2)1n=11(n+1)2=n=2(1)nn2=n=1(1)nn2+1letfindn=1(1)nn2wehaven=1(1)nn2=n=11(2n)2n=01(2n+1)2=14π26n=01(2n+1)2butn=11n2=14n=11n2+n=01(2n+1)2n=01(2n+1)2=34Σ1n2=34π26=π28n=1(1)nn2=π224π28=π21201ln(x)ln(1+x)dx=ln(2)ln(2)+1(π212+1)=π2122ln(2).

Answered by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

∫_0 ^1 ln(1+x)×ln(x)dx  ≈−0.21(approx)

01ln(1+x)×ln(x)dx0.21(approx)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com